Penerapan Soccer Like Games Melalui Game Based Learning dalam Meningkatkan Kemampuan Bermain Siswa di SMAN 1 Cibatu - Reival Erpati Denis; Bambang Abduljabar; Reshandi Nugraha (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the effectiveness of applying soccer like games through game based learning in improving the playing ability of grade XI students at SMAN 1 Cibatu. The method used is quantitative descriptive with a one group test design. The research subjects amounted to 29 students who were selected using random sampling techniques. The measurement instrument used the Game Performance Assessment Instrument (GPAI). The results showed (1) an increase in the average score from 63.22 in the pretest to 75.00 in cycle 1 and 83.05 in the posttest; (2) an increase in the completeness percentage from 34.5% to 65.5% and 89.7%; (3) an N-Gain value of 0.54, categorized as 'medium'; and (4) the application of soccer like games through GBL proved effective in improving students' playing skills gradually and in a structured manner. Keywords: Game Based Learning, Playing Ability, Soccer Like Games